1992
DOI: 10.1104/pp.99.2.681
|View full text |Cite
|
Sign up to set email alerts
|

Photooxidative Destruction of Chloroplasts Leads to Reduced Expression of Peroxisomal NADH-Dependent Hydroxypyruvate Reductase in Developing Cucumber Cotyledons

Abstract: Photooxidative destruction of chloroplasts by exposure of norflurazon-treated cucumber (Cucumis sativus L.) seedlings to white light leads to reduced levels of the nuclear-encoded, peroxisomal enzyme hydroxypyruvate reductase. The partial reduction in hydroxypyruvate reductase activity under photooxidative conditions is accompanied by reductions in levels of hydroxypyruvate reductase protein and transcript. The low level of hydroxypyruvate reductase gene expression in the dark is not affected by norflurazon, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…This time-dependent component may be due to the stimulatory effect of a photosynthetic product that is produced at a constant rate during irradiation. This possibility is supported by our previous demonstration that intact chloroplasts are required for Hpr expression (Schwartz et al, 1992) and may reflect the need for an adequate rate of phosphoglycolate metabolism during active photosynthesis.…”
Section: Discussionsupporting
confidence: 72%
“…This time-dependent component may be due to the stimulatory effect of a photosynthetic product that is produced at a constant rate during irradiation. This possibility is supported by our previous demonstration that intact chloroplasts are required for Hpr expression (Schwartz et al, 1992) and may reflect the need for an adequate rate of phosphoglycolate metabolism during active photosynthesis.…”
Section: Discussionsupporting
confidence: 72%
“…This results in acoordinate loss of both chloroplast function and CAB transcription in the nucleus (Oelmtiller, 1989;Susek and Chory, 1992). The accumulation of nuclear-encoded transcripts for nitrate reductase and hydroxypyruvate reductase is also sensitive to photobleaching, even though they encode nonchloroplast proteins with functions related to photosynthesis (OelmDller and Briggs, 1990;Schwartz et al, 1991). In other studies, nitrogen starvation or the inhibition of plastid transcription or translation from the time of germination blocks CAB messenger RNA (mRNA) accumulation (Oelmiiller et al, 1986;Taylor et al, 1987;Plumley and Schmidt, 1989;Taylor, 1989;Mathews and Durbin, 1990;Rapp and Mullet, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…112,1996 our laboratory. We previously showed that white-lightdependent Hpr expression in cucumber requires the presente of functional chloroplasts (Schwartz et al, 1992). Later work showed that a 4-h irradiation period is sufficient to stimulate maximal Hpr mRNA accumulation, and that for irradiations shorter than 4 h, the peak level of Hpr mRNA is directly proportional to the length of the irradiation period (Bertoni and Becker, 1993).…”
Section: Discussionmentioning
confidence: 99%